Thermal conductivity of argon–SiO2 cryocrystal nanocomposite - Nikonkov, R.V.; Stachowiak, P.; Jeżowski, A.; Krivchikov, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The effective thermal conductivity of samples of cryocrystal nanocomposite obtained from argon and SiO2 nanopowder was determined in the temperature interval 2–35 K using the steady-state method. The thermal conductivity of crystalline argon with nanoparticles of amorphous silica oxide embedded in its structure shows a weak dependence on particle linear dimension in the interval 5–42 nm. The temperature dependence of the thermal conductivity of the nanocomposites can be well approximated by taking into account only the two mechanisms of heat carrier scattering: phonon-phonon interaction in U-processes and scattering of phonons by dislocations.